Mixed Problem with an Integral Two-Space-Variables Condition for a Class of Hyperbolic Equations. (30th January 2013) - Oussaeif, Taki-Eddine; Bouziani, Abdelfatah
Abstract : This paper is devoted to the proof of the existence and uniqueness of the classical solution of mixed problems which combine Neumann condition and integral two-space-variables condition for a class of hyperbolic equations. The proof is based on a priori estimate "energy inequality" and the density of the range of the operator generated by the problem considered.